The Effects of Propolis and its Isolated Compounds on Cytokine Production by Murine Macrophages - Bachiega, Tatiana Fernanda [UNESP]; Orsatti, C. L. [UNESP]; Pagliarone, A. C. [UNESP]; Sforcin, J. M. [UNESP] (Wiley-Blackwell, 2012)
Since propolis and phenolic compounds, such as cinnamic and coumaric acids, have several biological properties, their immunomodulatory effect on cytokine production (IL-1 beta, IL-6 and IL-10) was investigated. Peritoneal macrophages from BALB/c mice were incubated with propolis, coumaric and cinnamic acids in different concentrations and the concentrations that inhibited cytokine production were tested before or after macrophage challenge with LPS, to evaluate a possible immunomodulatory action. Propolis and the acids stimulated IL-1 beta production, while IL-6 production was significantly inhibited after incubation with propolis (5, 50 and 100 mu g/well), coumaric and cinnamic acids (50 and 100 mu g/well). In LPS-challenge protocols, inhibitory concentrations of cinnamic and coumaric acids after LPS incubation prevented efficiently its effects on IL-6 production, whereas propolis inhibited LPS effects both before and after its addition. Propolis, coumaric and cinnamic acids (50 and 100 mu g/well) inhibited IL-10 production as well. Both acids showed a similar inhibitory activity on IL-10 production when added after LPS challenge, while propolis counteracted LPS action when added before and after LPS incubation. Propolis modulated the immune/inflammatory response, depending on the concentration. Its efficiency may occur due to the synergistic effect of its compounds, and cinnamic and coumaric acids may be involved in the action of propolis on cytokine production. Copyright (C) 2012 John Wiley & Sons, Ltd.
Keywords: propolis; immunomodulation; cytokines; cinnamic acid; coumaric acid